Gas6 expression and Tyrosine kinase Axl Sky receptors: Their relation with tumor stage and grade in patients with bladder cancer - TİNAY, İLKER; ÖZYÜREK, MUSTAFA (PAGEPRESS PUBL, 2021)
Objectives: It has been shown that the dys-regulation of tyrosine kinase Axl receptor and its ligand growth arrest-specific gene (Gas6) are associated with poor prognosis in various types of tumors but there is not enough study about their importance in bladder cancer (BC). We evaluated the relation of Gas6 gene expression and tyrosine-kinase Axl and Sky (Tyro 3) receptors with tumor stage and grade in patients with BC. Material and Methods: The study group consists of 55 patients whose transurethral resection of bladder (TUR-B) has been performed due to RC and the control group consists of 12 patients with normal bladder mucosa. In tissues mRNAs of Gas6, Axl, and Sky receptors were examined by quantitative (Real-Time) PCR (qPCR). Protein expression was measured by immunohistochemistry. Plasma Gas6 protein levels were compared with control group by ELISA method. Results: Patients with BC were grouped as Ta low (n=17), Ta high (n=5), T1 low (n=9), T1 high (n=8) and T2 (n=16) according to their TUR-B pathologies. The qPCR analysis showed that the expression of Gas6 gene and AxI receptor is higher in the tumor-positive group and the immune-histochemical showed that the bladder samples of the tumor-positive group stained significantly positive. When the patients are grouped according to the TUR-B pathologies, a statistical significant difference was observed among groups in the qPCR analysis ratios of Gas6 gene and Axl receptor by (p < 0.05) but no significance was found for Sky receptor (p > 0.05). When Gas6 protein levels in plasma samples were compared by ELISA method, a statistical significance was determined among groups (p = 0.001). Conclusions: Our findings indicate that mRNAs of Gas6 and Axl receptor are closely related to tumor stage and grade in patients with BC. Further studies are needed for understanding the role of Gas6 and its receptors on the neoplastic transformation in terms of novel biomarkers and potential therapeutic targets.
Keywords: Bladder cancer; Gas6; Axl; Sky; Tyro3; PROTEIN; ACTIVATION; PROMOTES